Deoxycytidine and deoxythymidine treatment for thymidine kinase 2 deficiency. - López-Gómez, Carlos; Levy, Rebecca J; Sánchez-Quintero, María José; Juanola-Falgarona, Martí; Barca, Emanuele; Garcia Diaz, Beatriz; Tadesse, Saba; Garone, Caterina; Hirano, Michio (Wiley, 2017)
Objective—Thymidine kinase 2 (TK2), a critical enzyme in the mitochondrial pyrimidine salvage pathway, is essential for mitochondrial DNA (mtDNA) maintenance. Mutations in the nuclear gene TK2 cause TK2 deficiency, which manifests predominantly in children as myopathy with mtDNA depletion. Molecular bypass therapy with the TK2 products, dCMP and dTMP, prolongs the lifespan of Tk2-deficient (Tk2-/-) mice by 2-3 fold. Because we observed rapid catabolism of the deoxynucleoside monophosphates to deoxythymidine (dT) and deoxycytidine (dC), we hypothesized that: 1) deoxynucleosides might be the major active agents and 2) inhibition of deoxycytidine deamination might enhance dTMP+dCMP therapy. Methods—To test these hypotheses, we assessed two therapies in Tk2-/- mice: 1) dT+dC and 2) co-administration of the deaminase inhibitor, tetrahydrouridine (THU), with dTMP+dCMP. Results—We observed that dC+dT delayed disease onset, prolonged lifespan of Tk2-deficient mice, and restored mtDNA copy number as well as respiratory chain enzyme activities and levels. In contrast, dCMP+dTMP+THU therapy decreased lifespan of Tk2-/- animals compared to dCMP +dTMP.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/7599
Keywords: Patología mitocondrial - Tratamiento; ADN mitocondrial; Patología mitocondrial - Mutación; TK2 deficiency; Mitochondrial DNA; Deoxycytidine; Deoxythymidine; Therapy